EVALUATION OF MORPHOLOGICAL CHARACTERS AND ASSESMENT OF DNA CONTENT USING FLOWCYTOMETRY ANALYSIS IN REGENERANTS DWARF NAPIERGRASS FROM EMBRYOGENIC CALLI - Nafiatul Umami, N. Umami (Himpunan Ilmuwan Tumbuhan Pakan Indonesia (HITPI), 2013)
Callus is an excellent source for in uifro plant regeneration, but plants regenerated from cailr:; son:letimes show phenotypic and geno$pic variation from the initial plants. In this study, there was no variations betlveen regenerated plants and dwarf napiergrass as control. Research result on six morphologicai char*i:;eis rlid not show differences between regenerated plants and control plants. There were not either significant ,.iii'ier'*::ces of DNA content between control and regenerated plants. The method established by this research was a sii:htre anll efficient method that can be applied for suppiying transformation materials using callus. Key utords : Callus, morphological characteristic, dusarf napiergrass